A Metro Optimized Braking Project for Metro Vehicle - SHENG Lu-ping; ZHANG Yu-fu; ZHANG Hong-jiang; YU Xiao-jie (机车电传动)
Wire-contol mode majoring braking control project and network-control mode majoring braking control project using in metrowere compared and analyzed, and an optimized braking project based on network control was presented. For this project, 100% braking wasexecuted when network or wire instruction was abnormal, which improved brake system reliability.